Nocturnal respiratory abnormalities among ward-level postoperative patients as detected by the Capnostream 20p monitor: A blinded observational study. - Vichaya Champreeda; Raymond Hu; Brandon Chan; Owen Tomasek; Yuan-Hong Lin; Laurence Weinberg; Will Howard; Chong O Tan (PLoS ONE, 2023)
Purpose This prospective observational study aimed to establish the frequency of postoperative nocturnal respiratory abnormalities among patients undergoing major surgery who received ward-level care. These abnormalities may have implications for postoperative pulmonary complications (PPCs). Methods Eligible patients underwent blinded noninvasive continuous capnography with pulse oximetry using the Capnostream™ 20p monitor over the first postoperative night. All patients received oxygen supplementation and patient-controlled opioid analgesia. The primary outcome was the number of prolonged apnea events (PAEs), defined as end-tidal carbon dioxide (EtCO2) ≤5 mmHg for 30-120 seconds or EtCO2 ≤5 mmHg for >120 seconds with oxygen saturation (SpO2) <85%. Secondary outcomes were the proportion of recorded time that physiological indices were aberrant, including the apnea index (AI), oxygen desaturation index (ODI), integrated pulmonary index (IPI), and SpO2. Exploratory analysis was conducted to assess the associations between PAEs, PPCs, and pre-defined factors. Results Among 125 patients who had sufficient data for analysis, a total of 1800 PAEs occurred in 67 (53.4%) patients. The highest quartile accounted for 89.1% of all events. Amongst patients who experienced any PAEs, the median (IQR) number of PAE/patient was four (2-12). As proportions of recorded time (median (IQR)), AI, ODI, and IPI were aberrant for 12.4% (0-43.2%), 19.1% (2.0-57.1%), and 11.5% (3.1-33.3%) respectively. Only age, ARISCAT, and opioid consumption/kg were associated with PPCs. Conclusions PAE and aberrant indices were frequently detected on the first postoperative night. However, they did not correlate with PPCs. Future research should investigate the significance of detected aberrations.